North Carolina - Hintz, Martin; Hintz, Stephen V. (New York : Children's Press, 1998)
An introduction to the geography, history, natural resources, economy, people, and interesting sites of North Carolina.
Includes bibliographical references (p. 136) and index.
8.9
5-8
Keywords: North Carolina -- Juvenile literature; North Carolina; North Carolina